Anxiety and its complications after the COVID-19 pandemic (Research, Society and Development, 2023)
It is important to consider the impact that the COVID-19 pandemic has as a multidimensional stressor, potentially toxic to individuals' mental health. Therefore, this research aimed to describe complications associated with anxiety after the COVID-19 pandemic. Bibliographical research of the integrative review type was carried out in the MEDLINE, LILACS and BDEnf databases in order to locate original articles available for reading, published between 2020 and 2023 and that discuss the consequences of post-pandemic anxiety. The following descriptors were used: Anxiety, COVID-19 and Adaptation Psychological. Repeated articles, literature reviews, monographs, dissertations or theses were excluded. After selecting the studies, a synthesis matrix was constructed for data collection so that they could be grouped and analyzed through critical analysis. The final sample was made up of six articles that highlighted the consequences of COVID-19 on mental health, with an emphasis on anxiety due to the economic and health crisis generated by the pandemic. All authors recognize that the pandemic has had significant impacts on people's mental health, highlighting the need for interventions to promote mental well-being in different contexts, including families, schools, communities and societies in general. There has been a significant increase in other mental health challenges such as school absences, excessive substance use, sleep disturbances and eating disorders. The implications of this post-pandemic anxiety span a wide range of areas of mental health, including increased stress, persistent worries, emotional challenges, and even the correlation with aggressive behaviors.